Give My Regards to Eighth Street: Collected Writings of Morton Feldman - Feldman, Morton 1926-1987; Friedman, B.H. (Cambridge Exact Change, 2000)
Morton Feldman (1926-1987) is among the most influential American composers of the 20th century. While his music is known for its extreme quiet and delicate beauty, Feldman himself was famously large and loud. His writings are both funny and illuminating, not only about his own music but about the entire New York School of painters, poets, and composers that coalesced in the 1950s, including his friends Jackson Pollock, Philip Guston, Mark Rothko, Robert Rauschenberg, Frank O'Hara, and John Cage. Give My Regards to Eighth Street is an authoritative collection of Feldman's writings, culled from published articles, program notes, LP liners, lectures, interviews, and unpublished writings.
Keywords: Music history